Design of Automated Processing Equipment Shallots (PEBMO) To Improve Product Quality Shallots - Indrawati, Elsanda Merita; Munawi, Hisbulloh Ahlis; Suwardono, Agus; Santoso, Rachmad (Universitas Malikussaleh, 2019)
For farmers onion, red onion quality is required to be maintained and prioritized, as the quality affect the selling price in the market. There are three types of quality of onion, which is of high quality red onion, red onion, medium quality and low quality onion. The third quality of onion was always found in every harvest, only a percentage of each crop are changing in every quality. Onion have lower quality will have a selling price is also very low, this has resulted in farmers losing money if yields lower quality onions have a high percentage. The best way to overcome the loss factor is to cultivate the red onion into a low-quality food products of high quality, so for that tool